Wearable Robotics: Challenges and Trends c - Moreno, Juan C.; Masood, Jawad; Schneider, Urs.; Maufroy, Christophe; Pons, Jose L.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book reports on advanced topics in the areas of wearable robotics research and practice. It focuses on new technologies, including neural interfaces, soft wearable robots, sensors and actuators technologies, discussing industrially and medically-relevant issues, as well as legal and ethical aspects. It covers exemplary case studies highlighting challenges related to the implementation of wearable robots for different purposes, and describing advanced solutions. Based on the 5th International Symposium on Wearable Robotics, WeRob2020, and on WearRacon Europe 2020, which were both held online on October 13-16, 2020, the book addresses a large audience of academics and professionals working in for the government, in the industry, and in medical centers, as well as end-users alike. By merging together engineering, medical, ethical and industrial perspectives, it offers a multidisciplinary, timely snapshot of the field of wearable technologies. .
Chapter 1: What should we expect from passive exoskeletons -- Chapter 2: Balance recovery support using wearable robotic devices -- Chapter 3: Active Life with Prosthesis -- Chapter 4: Legislation, safety and performance: regulatory aspects in wearable robots -- Chapter 5: The testing of industrial exoskeletons -- Chapter 6: Evidenced-based Indications/Contraindications for and Potential Benefits of Exoskeletal-Assisted Walking in Persons with Spinal Cord Injury.
Keywords: Biomedical engineering; User interfaces (Computer systems).; Human-computer interaction; Robotics; Biomechanics; Biomedical Devices and Instrumentation; User Interfaces and Human Computer Interaction; Medical and Health Technologies; Robotic Engineering; Biomechanical Analysis and Modeling; Robotics; Wearable Electronic Devices; Exoskeleton Device; Biosensing Techniques; Ethics, Medical; Congress